Naringenin Nano-Delivery Systems and Their Therapeutic Applications - Bhia, Mohammed (2021)
Naringenin (NRG) is a polyphenolic phytochemical belonging to the class of flavanones and is widely distributed in citrus fruits and some other fruits such as bergamot, tomatoes, cocoa, and cherries. NRG presents several interesting pharmacological properties, such as anti-cancer, anti-oxidant, and anti-inflammatory activities. However, the therapeutic potential of NRG is hampered due to its hydrophobic nature, which leads to poor bioavailability. Here, we review a wide range of nanocarriers that have been used as delivery systems for NRG, including polymeric nanoparticles, micelles, liposomes, solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), nanosuspensions, and nanoemulsions. These nanomedicine formulations of NRG have been applied as a potential treatment for several diseases, using a wide range of in vitro, ex vivo, and in vivo models and different routes of administration. From this review, it can be concluded that NRG is a potential therapeutic option for the treatment of various diseases such as cancer, neurological disorders, liver diseases, ocular disorders, inflammatory diseases, skin diseases, and diabetes when formulated in the appropriate nanocarriers.